2014
DOI: 10.1073/pnas.1318848111
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional ectodermal stem cells around the nail display dual fate homeostasis and adaptive wounding response toward nail regeneration

Abstract: Regulation of adult stem cells (SCs) is fundamental for organ maintenance and tissue regeneration. On the body surface, different ectodermal organs exhibit distinctive modes of regeneration and the dynamics of their SC homeostasis remain to be unraveled. A slow cycling characteristic has been used to identify SCs in hair follicles and sweat glands; however, whether a quiescent population exists in continuously growing nails remains unknown. Using an in vivo label retaining cells (LRCs) system, we detected an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 30 publications
(43 reference statements)
4
49
1
Order By: Relevance
“…3A) [37]. In agreement with this, a recent study using the LRC technique identified nail stem cells within the basal layer of the PNF, organized in a ring-like configuration around the nail root [38].…”
Section: Nail Stem Cellssupporting
confidence: 75%
See 1 more Smart Citation
“…3A) [37]. In agreement with this, a recent study using the LRC technique identified nail stem cells within the basal layer of the PNF, organized in a ring-like configuration around the nail root [38].…”
Section: Nail Stem Cellssupporting
confidence: 75%
“…By contrast, in alopecia areata, which is regarded as a T cell-mediated autoimmune disease, it was suggested that IP collapse in the anagen hair bulb may be induced by upregulation of interferon-gamma, triggers of which include infection and psychoemotional stress [45]. [38] (mouse), proximal NM [24] (mouse), distal NM [23] (mouse). (B) Immune privilege (IP) in the hair follicle and the nail unit.…”
Section: Immunology Of the Nailmentioning
confidence: 99%
“…Instead, they found label-retaining cells within the proximal nail fold that give rise to the eponychium during homeostatic conditions. They also showed that, during long-term growth or wounding/regenerative conditions, these cells have a binary potential and can differentiate into the nail plate, thus leading to the conclusion that the proximal nail fold harbors nail stem cells (35). Although these data are seemingly in conflict with both the preexisting literature as well as the data we present in this article, the differences in experimental markers and timing of pulses/ analyses can rectify most of the discrepancies.…”
Section: Discussionmentioning
confidence: 57%
“…We confirm that the nail matrix gives rise to the nail plate, and in addition, we show that Lgr6 is a molecular marker specific to the nail stem cells. Interestingly, Leung et al recently performed a Keratin5 TetOff ;TreH2BGFP pulse-chase experiment to identify label-retaining cells in the digit tip and did not find a presumptive stem cell population within the nail matrix (35). Instead, they found label-retaining cells within the proximal nail fold that give rise to the eponychium during homeostatic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation